Socially and Economically Vulnerable Women: Building Strategies to Move Out of Poverty - Willya Achmad (IKIP Mataram, 2023)
This research aims to identify strategies that can help socially and economically vulnerable women to escape poverty. Through a qualitative approach, with a descriptive method to analyze vulnerable social and economic conditions. This research uses qualitative methods through literature study. The stages of this research were carried out by gathering literary sources obtained from various books, journals, program documents, activity reports, thesis and dissertation research results, as well as online news sources from the internet which were considered relevant and credible to become the source of data in this research. Data analysis technique use the content analysis method. The research results show that there are several effective strategies in helping vulnerable women escape poverty , such as building skills and education, strengthening social networks, and utilizing available local resources. However, this study also found several obstacles in implementing this strategy, such as a lack of access to resources and difficulties in accessing social services. This research makes an important contribution to efforts to improve the welfare of women who are socially and economically vulnerable, as well as provide recommendations for policies that are more inclusive and pro-vulnerable.